Exploration of the 3D World on the Internet Using Commodity Virtual Reality Devices - Nguyen, Minh; Tran, Huy; Le, Huy (Multimodal technologies and interaction, 2017)
This article describes technical basics and applications of graphically interactive and online Virtual Reality (VR) frameworks. It automatically extracts and displays left and right stereo images from the Internet search engines, e.g., Google Image Search. Within a short waiting time, many 3D related results are returned to the users regarding aligned left and right stereo photos; these results are viewable through VR glasses. The system automatically filters different types of available 3D data from redundant pictorial datasets on the public networks (the Internet). To reduce possible copyright issues, only the search for images that are “labelled for reuse” is performed; meaning that the obtained pictures can be used for any purpose, in any area, without being modified. The system then automatically specifies if the picture is a side-by-side stereo pair, an anaglyph, a stereogram, or just a “normal” 2D image (not optically 3D viewable). The system then generates a stereo pair from the collected dataset, to seamlessly display 3D visualisation on State-of-the-art VR devices such as the low-cost Google Cardboard, Samsung Gear VR or Google Daydream. These devices are used to provide an immediate, controllable 3D display. In this article, we propose an image type classification technique that dynamically extracts co-aligned stereo pairs with rich 3D visualisation to VR viewers. This system is portable, simple to set up and operate. From some initial experiment results; our system is shown to be relatively fast, accurate, and easy to implement. With such system, Internet users all over theWorld could easily visualise millions of real life stereo datasets publicly available on the Internet; which are believed to be useful for VR testing and learning purposes.